Glycogen-rich clear cell carcinoma of the feline mammary gland: Case report - Campos, C. B. [UNESP]; Gamba, C. O.; Damasceno, K. A.; Lavalle, G. E.; Cassali, G. D. (FapUNIFESP (SciELO), 2016)
The aim of this report is to describe the first histopathological, immunohistochemical, and clinical characteristics of a feline glycogen-rich clear cell carcinoma (GRCCC). A Persian queen was admitted with mammary gland tumors and underwent radical unilateral mastectomy. Overall survival was considered 33 days and death was due to clinical evolution of the disease. Microscopic evaluation demonstrated epithelial cells arranged in a predominantly solid pattern, tumor cells presented an ample, granular, and foamy clear cytoplasm, and moderate cellular pleomorfism. The presence of cytoplasmatic glycogen was confirmed through diastase digestion followed by PAS staining. Histopathological and histochemical findings lead to the diagnosis of GRCCC with regional metastases.
Keywords: Feline; Glycogen-rich clear cell carcinoma; Mammary gland; Neoplasm